Biomapping of Microbial Indicators on Beef Subprimals Subjected to Spray or Dry Chilling over Prolonged Refrigerated Storage - Diego E. Casas; Rosine Manishimwe; Savannah J. Forgey; Keelyn E. Hanlon; Markus F. Miller; Mindy M. Brashears; Marcos X. Sanchez-Plata (Foods, 2021)
As the global meat market moves to never frozen alternatives, meat processors seek opportunities for increasing the shelf life of fresh meats by combinations of proper cold chain management, barrier technologies, and antimicrobial interventions. The objective of this study was to determine the impact of spray and dry chilling combined with hot water carcass treatments on the levels of microbial indicator organisms during the long-term refrigerated storage of beef cuts. Samples were taken using EZ-Reach™ sponge samplers with 25 mL buffered peptone water over a 100 cm2 area of the striploin. Sample collection was conducted before the hot carcass wash, after wash, and after the 24 h carcass chilling. Chilled striploins were cut into four sections, individually vacuum packaged, and stored to be sampled at 0, 45, 70, and 135 days (n = 200) of refrigerated storage and distribution. Aerobic plate counts, enterobacteria, Escherichia coli, coliforms, and psychrotroph counts were evaluated for each sample. Not enough evidence (p > 0.05) was found indicating the hot water wash intervention reduced bacterial concentration on the carcass surface. E. coli was below detection limits (<0.25 CFU/cm2) in most of the samples taken. No significant difference (p > 0.05) was found between coliform counts throughout the sampling dates. Feed type did not seem to influence the (p > 0.25) microbial load of the treatments. Even though no immediate effect was seen when comparing spray or dry chilling of the samples at day 0, as the product aged, a significantly lower (p < 0.05) concentration of aerobic and psychrotrophic organisms in dry-chilled samples could be observed when compared to their spray-chilled counterparts. Data collected can be used to select alternative chilling systems to maximize shelf life in vacuum packaged beef kept over prolonged storage periods.